Thermal modeling and empirical verification of multi unit small satellites - Anwar Ali; Muhammad Rizwan Mughal; Shoaib Ahmed Khan; Kar Seng Teng (Results in Engineering)
Recent developments in the miniaturization and cost reduction of small satellites have attracted the attention of researchers worldwide. The miniaturized and lightweight modular small satellites have resulted in an extensive range of multi-unit small satellites. The most challenging design aspect of the multi-unit small satellites is thermal control. In space environment, heat can be removed through conduction and radiations, because there is no heat convection, which further intensifies the need to ensure thermal stability during the design and development phases. In this paper, we present a thermal model of a small spacecraft power-management tile. Using the proposed thermal model, the thermal resistance is measured analytically for a single tile. The proposed model is applied to a single small-unit satellite structure and the resultant thermal resistance is measured. The analytically measured thermal resistances of the satellite is verified using an experimental setup. Furthermore, analytical techniques are applied to 4 U (4 units) and 8 U (8 units) multi-unit satellites. From the resultant lower value of thermal resistance, it is concluded that the heat absorbed by the spacecraft tile facing the sun is quickly dissipated to the opposite relatively cooler tile on the dark face and eventually radiates to the space environment. The proposed model is a useful tool for the preliminary design phase of a spacecraft design. By utilizing the proposed model, the designer can determine the type of material and its dimensions that can be used to obtain low thermal resistance of the spacecraft structure.